2019
DOI: 10.1093/neuonc/noz068
|View full text |Cite
|
Sign up to set email alerts
|

Association between hippocampal dose and memory in survivors of childhood or adolescent low-grade glioma: a 10-year neurocognitive longitudinal study

Abstract: Background Hippocampal avoidance has been suggested as a strategy to reduce short-term memory decline in adults receiving whole-brain radiation therapy (RT). The purpose of this study was to determine whether the hippocampal dose in children and adolescents undergoing RT for low-grade glioma was associated with memory, as measured by verbal recall. Methods Eighty patients aged at least 6 years but less than 21 years with low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 31 publications
1
37
1
Order By: Relevance
“…The aim of this contribution was to unsystematically highlight some methodological issues observed within the literature about the cognitive consequences of cranial irradiation for oncological management (Gondi et al, 2010 , 2012 , 2014 ; Kim et al, 2018 ; Acharya et al, 2019 ; Tringale et al, 2019 ). We advocate that much of the debate and many of the controversial results found within and across these studies are mainly based on such issues; the patients with disease of different clinical stages, the timing of neuropsychological assessment, and the absence of guidelines about the neuropsychological battery to employ for assessing the outcomes make it difficult to compare studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this contribution was to unsystematically highlight some methodological issues observed within the literature about the cognitive consequences of cranial irradiation for oncological management (Gondi et al, 2010 , 2012 , 2014 ; Kim et al, 2018 ; Acharya et al, 2019 ; Tringale et al, 2019 ). We advocate that much of the debate and many of the controversial results found within and across these studies are mainly based on such issues; the patients with disease of different clinical stages, the timing of neuropsychological assessment, and the absence of guidelines about the neuropsychological battery to employ for assessing the outcomes make it difficult to compare studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neurocognitive dysfunction was alternatively defined as a z -score drop of 1.5 (Gondi et al, 2012 ; Kim et al, 2018 ) or a decline of more than two standard deviations from the patient's own baseline value (Li et al, 2007 ). In other cases, the longitudinal trends of neurocognitive outcomes have been estimated by means of a regression analysis (Acharya et al, 2019 ).…”
Section: Clinical Significance: the Reliable Change Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…recent phase 2 study of young patients with low-grade glioma found a significant association between shortdelay recall and hippocampal volume receiving radiation. 6 Further prospective study of TVH avoidance in germinoma is warranted, with comprehensive review of all imaging at recurrence to permit correlation to irradiated volumes and longitudinal assessment of neurocognitive function.…”
Section: In Reply To Byun Et Almentioning
confidence: 99%
“…Worse still, Radiotherapy brings signi cant treatment-related side effects as cognitive dysfunction in the meantime of its controlling tumor recurrence according to a 12-year follow-up for patients below 40 years old [4]. A 10-year follow-up suggested that greater dose of radiotherapy was associated with a greater cognitive decline [5].…”
Section: Introductionmentioning
confidence: 99%